The Role of the Membrane-Initiated Heat Shock Response in Cancer - Bromberg, Zohar; Weiss, Yoram (Frontiers in Molecular Biosciences, 2016)
The heat shock response (HSR) is a cellular response to diverse environmental and physiological stressors resulting in the induction of genes encoding molecular chaperones, proteases and other proteins that are essential for protection and recovery from cellular damage. Since different perturbations cause accumulation of misfolded proteins, cells frequently encounter fluctuations in the environment which alter proteostasis. Since tumor cells use their natural adaptive mechanism of coping with stress and misfolded proteins, in recent years, the proteostasis network became a promising target for anti-tumor therapy. The membrane is the first to be affected by heat shock and therefore may be the first one to sense heat shock. The membrane also connects between the extracellular and the intracellular signals. Hence, there is a “cross talk” between the HSR and the membranes since heat shock can induce changes in the fluidity of membranes, leading to membrane lipid remodeling that occurs in several diseases such as cancer. During the last decade, a new possible therapy has emerged in which an external molecule is used that could induce membrane lipid re-organization. Since at the moment there are very few substances that regulate the HSR effectively, an alternative way has been searched to modulate chaperone activities through the plasma membrane. Recently, we suggested that the use of the membrane Transient Receptor Potential Vanilloid-1 (TRPV1) modulators regulated the HSR in cancer cells. However, the primary targets of the signal transduction pathway are yet un-known. This review provides an overview of the current literature regarding the role of HSR in membrane remodeling in cancer since a deep understanding of the membrane biology in cancer and the membrane heat sensing pathway is essential to design novel efficient therapies.